ANALISIS TERHADAP KASUS PEMBUNUHAN YANG TERJADI DI JAWA TENGAH AKIBAT PERSELINGKUHAN - Finsensius Samara; Ricardo Amaral; Anggi Boleng; Castyelo Sogen (Collegium Studiosum Journal, 2023)
The murder was committed because of infidelity. One example of a murder case or evidence is the murder that occurred in Brebes. This report was written with the aim of recording and providing explanations and providing suggestions for resolving the problems of this case. This research will be examined accurately and concisely, and the results will be presented in the form of a scientific article. The murder that occurred in Brebes is one of the newest cases that will occur in 2023. Law enforcement against the perpetrator must be responsible and comply with existing laws. The murder case in Brebes is a case that is attracting attention because it is still under suspicion. The research method used is a qualitative approach. This research uses primary and secondary legal material sources. The analysis technique used is a content analysis data analysis technique, namely a data analysis technique by examining the contents of secondary data that has been collected so that it is compiled, then explained from statutory material. The deductive thinking pattern is a way of thinking based on basic principles, then research presents the object to be studied in order to draw conclusions about specific facts.